TRASH to TREASURE: UTILIZING WASTE MATERIALS AS A MEDIUM of ENGLISH INSTRUCTION - Sondang Pondan Leoanak; Bonik Kurniati Amalo (IAIN Syekh Nurjati Cirebon, 2018)
Abstract: It is believed that teaching and learning experiences that involve the learner actively in practical examples are engaged longer than theoretical experiences. Instructional resources are teaching aids or media used to help teachers and students in classroom interaction. These aids help teachers to provide fun, interesting and enjoyable platform (effective presentation) to convey information of a given topic as a means of motivating students to achieve their learning objectives. In general, the present study aims to find out how the teachers in Rijalul Ghad Islamic school in Kera island, Kupang regency, East Nusa Tenggara Province, Indonesia utilized waste materials to support their teaching and learning process in the classroom. The data were collected using classroom observation, semi-structured interview with the teachers as well as the students as the respondents and a list 15-item of questions about the level of application in utilizing instructional media addressed to the teachers and the students. This study reveals that the students were active during the application of the instructional media using waste materials such as papers and drinking mineral bottles. In addition, during the application of the teaching and learning aids, the students also learnt how to work in team during group discussion and how to appreciate other’s opinion. However, a support on the use of teaching aids, especially teacher’s made (or teacher-students’ made) need to be increased among teachers. This is because, not all teachers are able to utilize waste materials in to instructional media